An unusual case of palatal swelling – Hyalinizing clear cell carcinoma: a case report. (6th June 2016) - Padayachee, N.; Martin, L.H.C.; Syyed, N.; Sood, V.; Carton, A.
Abstract: Hyalinizing clear cell carcinoma is an uncommon malignant salivary gland tumour that appears almost exclusively in the minor salivary glands of the oral cavity.1 2 It is an indolent tumour with little metastatic potential, and therefore, it is important to distinguish it from other, more aggressive, clear cell lesions such as metastatic renal cell carcinoma.3 We present the case of a 48‐year‐old woman who presented with a 2‐year history of a mass on her soft palate. The clinical history, imaging and histopathological features are described and discussed.